Interpretive Phenomenological Analysis of the Spiritual Characteristics of Recovery Experiences in the Context of the Brain Disease Model of Addiction - Kime, Katie Givens (Pastoral psychology, 2018)
Spirituality persists as a mechanism of behavior change for addiction recovery. The aim of this project was to carefully attend to how those in recovery construct meaning of their experience of addiction, regardless of the addiction treatment modality or ideological framework. Participant accounts reflected the increased public interest in and research funding based on the brain disease model of addiction (BDMA). The qualitative study used interpretive phenomenological analysis to investigate the experiences of six adults (age range from 24 to 72) with at least three years of sustained recovery from substance use disorders. In-depth key informant interviews tracked their construction of their experiences and their understanding of addiction. Participants who entered recovery after 2010 sought to integrate BDMA-related constructs into their understanding of addiction and recovery. Addiction recovery narratives featuring BDMA-related constructs integrated neuroscience-related ideas with spirituality-related constructs rather than completely replacing the latter. Notable innovations and paradoxical tensions were found within participant accounts. Such features echo the insights on secularity of Harvard philosopher Charles Taylor, particularly his notion of the buffered self, which offers a theoretical framework for understanding these shifts in meaning-making. For persons entering recovery in the twenty-first century, the brain disease model of addiction carries more explanatory authority than it does for previous generations, despite the lack of agreement across addiction-related neuroscientific findings. As a model, it engenders more mechanistic, agential, brain-centered (buffered) senses of self, ostensibly making it less compatible with spiritual understandings of addiction than other medical models of addiction. However, this study's findings indicate that those in recovery are likely to devise complex narratives of the etiology of addiction that combine elements from various models.